Onomastic Identification of Kaunas Noblemen in Military Records of Lithuanian Grand Duchy in 1528 - Čirūnaitė, Jūratė (Respectus Philologicus, 2018)
The article analyses the name record of Kaunas male and female noblemen compiled in 1528 in the Grand Duchy of Lithuania. The article also describes the constituent parts of the record of Kaunas noblemen, indicates the methods of presenting the designation of brothers and analyses male, female names and names of previous generation. The male names of previous generation are reconstructed from patronyms. The male names are grouped into Christian and non-Christian names. The data on the distribution of Christian male names and old two-root names among two generations is provided. The research data on the names of Kaunas noblemen as well as the noblemen and citizen of other GDL territories of the same period are compared. Female names are analysed. Male designations are differentiated by the ratio of names and potential surnames into the types of onomastics, which are differentiated by the ratio of different anthroponyms into methods of onomastics. Female designations are differentiated into the types of onomastics based on the ratio of names and family anthroponyms and into the methods of onomastics based on the ratio of different types of anthroponyms. The description of the methods of onomastics takes into consideration the prefixes used with male and female designations. The structure of male and female designations is analysed: the types of anthroponyms and prefixes are indicated, the prefixes grouped into specific types are presented. The onomastics are differentiated by the number of anthroponyms, the average length of onomastics is determined. Lithuanian affixes of anthroponyms are listed.
Keywords: Kaunas Powiat in the 16th Century; Anthroponym; Patronym